Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-50357
|View full text |Cite
|
Sign up to set email alerts
|

Loss Reduction in Compressor Cascades by Means of Passive Flow Control

Abstract: Secondary flow effects like the corner stall between the wall and the vane in a compressor stage are responsible for a large part of total pressure losses. An extensive experimental study of flow control in a highly loaded compressor cascade was performed in order to decrease the separation and reduce the losses by means of vortex generators. The vortex generators were attached at the surface of the cascade side walls. These flow control devices produce strong vortices, which enhance the mixing between the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Using side wall actuation mainly influences the secondary flow structures. It has been demonstrated that vortex generators on the side wall of a two-dimensional high-speed cascade can result in a reduced total pressure loss [8]. Blade actuators avoid flow separation on the blade itself.…”
Section: Introductionmentioning
confidence: 99%
“…Using side wall actuation mainly influences the secondary flow structures. It has been demonstrated that vortex generators on the side wall of a two-dimensional high-speed cascade can result in a reduced total pressure loss [8]. Blade actuators avoid flow separation on the blade itself.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Active flow control methods, such as boundary layer suction, [14][15][16] flow blowing, 17,18 plasma flow control 19,21 etc, have been applied to the control of compressor cascade corner separations over years. Meanwhile, the application of passive flow control methods, such as vortex generator, [22][23][24] endwall contouring 25 etc, as well as combination of passive and active control methods, 26 for corner separation control have been investigated with great efforts. To control the corner separation effectively, the design of both active and passive methods should be based on the in-depth understanding of flow structures in the compressor cascade flow passage and various efforts have been spared.…”
Section: Introductionmentioning
confidence: 99%
“…This high-speed compressor cascade model is designed by the research group DLR (German Aerospace Center) and has been used broadly to study the flow control of high-speed compressor cascade corner separations (see, for example, [4,5,[8][9][10]). Its main geometrical and aerodynamic parameters are shown in Table 1.…”
Section: Numerical Methods and Plasma Actuation Layoutsmentioning
confidence: 99%
“…Passive flow control methodologies such as boundary layer fences [4,5], non-axisymmetric endwall contouring [6,7], and vortex generators [8][9][10] etc. can effectively reduce the detrimental effects of corner separations on the design conditions.…”
Section: Introductionmentioning
confidence: 99%